Understanding the attitudes towards climate change in the context of trust in selected countries of Central and Eastern Europe - Deák, Zsuzsanna; Vaznonienė, Gintarė; Wojewódzka-Wiewiórska, Agnieszka (Serbian Journal of Management, 2024)
Although there is a growing trend in scientific and political discussions about how people feel about climate change in the context of trust, adequate research in this area is lacking in Central Eastern Europe (CEE). This article aims to determine whether trust is an important factor for the perception of climate change by the inhabitants of selected CEE countries. European Social Survey (ESS) Round 10 data were used, and a multivariable binary logistic regression method was applied. This paper considers three different dimensions of climate change, concern, personal norms, and attribution, as well as a composite indicator reflecting climate attitudes (skeptic or proponent). Four different models are presented that differ only in terms of their dependent variables, while the independent variable (trust) and the control variables (socio-demographic variables) are the same in all the cases. The results show that both personal and institutional trust are very low in the selected countries. Institutional trust was significant in all four models, while personal trust was significant in the environmental norm and skepticism models. Greater trust in institutions decreases the odds of being worried about climate change and increases the odds of having feelings of personal responsibility for climate change reduction. An increased level of personal or institutional trust increases one’s chances of being in the climate proponent group. Of the socio-demographic variables examined only political left-right scale did not affect attitudes significantly.